Rotation des postes, assignation temporaire et impact des absences dans une usine d’abattage et de transformation du porc - Anne Falardeau; Nicole Vézina (Perspectives Interdisciplinaires sur le Travail et la Santé)
Case study and activity analysis involve processes that generally fall into different fields, but that have many similarities. This paper tries to show in how far each activity can be reciprocally enriched from the knowledge and experience acquired in the otherAn ergonomic intervention took place in a porcine slaughterhouse, with the goal of describing job rotation management along with the use made of a rehabilitation measure known as temporary reassignment (TR). The aim of TR is to return workers who have been victims of workplace accidents or professional illnesses such as musculoskeletal disorders to their workplace. A further goal of the intervention was to understand how TR and job rotation are interdependent. In the porcine slaughterhouse concerned, the slaughter department workers had managed to set up a very complex job rotation system designed to maximize the possibility for changes in the rhythm and variation in the performance of working gestures, so as to prevent musculoskeletal disorders. Although it was agreed that older workers’ rotations could be limited to less physically demanding workstations, workers refused to allow their lighter workstations to be eliminated from rotation as part of TR management. This study highlights the difficulties of TR management when the number of absentees does not allow rotation to be maintained in a way that would produce a better balance between health and production.